Impact of Leadership and Empowerment on Performance of Employees in Rural Banks: A Special Reference to Chhattisgarh Rajya Gramin Bank: Exploring the Impact of Leadership and Empowerment on Employee Performance in Rural Banks: A Case Study of Chhattisgarh Rajya Gramin Bank (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Employees represent the organization in different spheres. They may create a positive or a negative image of the organization in front of the customers. It is known that a organization without leader is just like a boat without rudder. Leadership play a vital role in achieving organizational objective, this can be only possible if an organization is having a good leader and leadership style in an organization. A good leader can easily motivate its employees and can easily change individual interest to organizational interest. Thus, there is need of good leader in the organization to motivate the employees, guiding them in a proper direction for achieving the organizational objective. Also, if organizational wants to achieve its objective in a given time period they have to empower their employees, so that they are freely to do their work, take their own decision regarding the task allotted to them can be easily completed without and delay . The study is basically focused on the impact of leadership and empowerment on performance of employees of Chhattisgarh Rajya Gramin Bank.